1997
DOI: 10.1179/mdh.1997.22.1.35
|View full text |Cite
|
Sign up to set email alerts
|

'My Plundered Townes, My Houses Devastation': The Civil War and North Midlands Life, 1642 - 1646

Abstract: This article will examine the effects on life in the north midlands during the first civil war, 1642 -1646, and relate these to the absence of clubmen risings in the region. In recent years historians have offered various explanations for the risings of the neutralist clubmen in the south west and south and west midlands during 1645.2 The most recent of these goes farther and attempts to explain why there were no such risings in other areas. Simon Osborne's 1994 article in 'Mifffarnf J-{j.story, offers a multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…138 Martyn Bennett, Ian Gentles and Mark Stoyle have all shown that the conflict in England could often be as vicious as anywhere else in the British Isles, particularly when aggravated by ethnic tensions. 132 Other historians remain unconvinced: John Morrill has opined as recently as 2017 that 'the civil war in England was not so very uncivilized', and that 'the number of men in arms killed in cold blood [was] very limited'; while Blair Worden has written that the 'awareness of common nationhood was a restraining bond', and that 'ties of kinship and friendship that crossed party lines held savagery back.' 133 The case study of Shelford House challenges this traditional view, at the same time as demonstrating how the social forgetting of the massacre could allow such a narrative to emerge.…”
Section: ***mentioning
confidence: 99%
“…138 Martyn Bennett, Ian Gentles and Mark Stoyle have all shown that the conflict in England could often be as vicious as anywhere else in the British Isles, particularly when aggravated by ethnic tensions. 132 Other historians remain unconvinced: John Morrill has opined as recently as 2017 that 'the civil war in England was not so very uncivilized', and that 'the number of men in arms killed in cold blood [was] very limited'; while Blair Worden has written that the 'awareness of common nationhood was a restraining bond', and that 'ties of kinship and friendship that crossed party lines held savagery back.' 133 The case study of Shelford House challenges this traditional view, at the same time as demonstrating how the social forgetting of the massacre could allow such a narrative to emerge.…”
Section: ***mentioning
confidence: 99%